(untitled) - Earhart, H. Byron (Belmont, Calif., 1969)
In continuous print since 1969, this text has helped establish the treatment of Japanese religion as a unified worldview, offering a concise yet thorough look at the culture and history of the Japanese religion. This text helps students see Japanese religion as a whole, rather than as disconnected religious traditions. No technical knowledge of Japanese history, Japanese religion, or the Japanese language is required for understanding the material. JAPANESE RELIGION has been used in Japan and Europe, as well as in North America
Keywords: Japan; Religious